Castrum Lubenov - Arkadiusz Michalak (Fasciculi Archaeologiae Historicae)
Due to illegal construction works in 2016, the late medieval motte-and-bailey castle in Lubrza was significantly damaged. The immediately undertaken rescue excavations paradoxically led to better understanding of the complex based on the obtained archaeological evidence as well as written sources, architectural studies, and remote sensing data. Detailed analysis of the artefacts has made it possible to establish the basic occupations of the inhabitants of the tower, their standard of living, everyday life, wealth, diet, and social status. The archaeological research also allowed us to establish accurate chronology of the complex, which should be placed in the 14th century.